2022
DOI: 10.21037/apm-22-201
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting sarcopenia in older patients with chronic diseases

Abstract: Background: Sarcopenia is an age-related disease characterized by a progressive loss of systemic muscle mass and/or decreased muscle strength and physical function. The occurrence of sarcopenia in patients with chronic diseases will not only cause further deterioration of diseases and adverse clinical outcomes, but also lead to high medical cost, suggesting a necessity and a great significance to explore the associated factors of sarcopenia in chronic patients in order to improve their quality of life. This st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 46 publications
0
25
0
Order By: Relevance
“…Alone, IGF-1 specificity for the diagnosis of sarcopenia is low, although IGF-1 has shown promising features in diagnosing sarcopenia when combined with a panel of biochemical markers [122]. Nevertheless, studies have shown that IGF-1 is lower in sarcopenic persons [122][123][124], correlates with muscle mass, hand grip strength, and gait speed [30,125] and is increased upon long-term resistance training [126].…”
Section: Hormonesmentioning
confidence: 99%
“…Alone, IGF-1 specificity for the diagnosis of sarcopenia is low, although IGF-1 has shown promising features in diagnosing sarcopenia when combined with a panel of biochemical markers [122]. Nevertheless, studies have shown that IGF-1 is lower in sarcopenic persons [122][123][124], correlates with muscle mass, hand grip strength, and gait speed [30,125] and is increased upon long-term resistance training [126].…”
Section: Hormonesmentioning
confidence: 99%
“…A cohort survey by Nishikawa et al (87) found that serum zinc concentration was positively correlated with HGS in patients with chronic kidney disease, and zinc deficiency patients with chronic kidney disease had a higher susceptibility to sarcopenia. The study by Xu et al (88) found that the serum zinc content of people without sarcopenia was much higher than that of people with sarcopenia and was positively correlated with relative skeletal muscle mass index (RSMI), indicating that zinc and iron may play an important role in the development and progression of sarcopenia. As we all know, zinc, as an essential trace element, is crucial to human growth and development, immunity, metabolism, and other physiological functions.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, decreased levels of IGF-1 have been found to be associated with sarcopenia in various disease states (48)(49)(50). Xu et al (51) found that patients with sarcopenia were older (P < 0.001) and had significantly lower IGF-1 levels (P < 0.01) through measuring the hormone levels of patients, suggesting that aging may affect IGF-1 levels. This is the same result as the study by Naro et al (52).…”
Section: Decreased Protein Synthesismentioning
confidence: 99%